Flavonoid Intake From Cocoa-Based Products and Adiposity Parameters in Adolescents in Spain - Laveriano-Santos, Emily P.; Arancibia-Riveros, Camila; Tresserra-Rimbau, Anna; Castro-Barquero, Sara; Ruiz-León, Ana María; Estruch, Ramón; Casas, Rosa; Bodega, Patricia; de Miguel, Mercedes; de Cos-Gandoy, Amaya; Martínez-Gómez, Jesús; Rodríguez, Carla; et al. (Frontiers in Nutrition, 2022)
Background: Cocoa-based products are a good source of flavonoids, which may have beneficial effects on metabolic health. Objective: To assess the relationship between flavonoids from cocoa-based products and adiposity parameters in adolescents. Methods: A cross-sectional study was conducted involving 944 adolescents aged 11 to 14 years enrolled in the SI! Program for Secondary Schools trial in Spain with available baseline data from food frequency questionnaires and anthropometric measurements (weight, height, waist circumference (WC), and fat mass percentage (% FM) by bioimpedance analysis). Fat mass index (FMI) and waist-to-height ratio (WHtR) were obtained by dividing fat mass by height, and WC by height, respectively. Body mass index (BMI), WC, and FMI for age and gender z-score were calculated. Overweight/obesity was defined as BMI ≥ 85th percentile, and excess adiposity as %FM or FMI ≥ 75th percentile. WC ≥ 90th percentile and WHtR with a 0.5 threshold were considered as criteria of abdominal obesity. Multilevel mixed-effect regressions were used to evaluate the association between flavonoids from cocoa-based products and adiposity parameters. Municipalities and schools were considered as random effects. Results: Participants with a higher flavonoid intake from cocoa-based products had lower WC z-score (B= -0.04, 95% CI (-0.07; -0.01), P-for trend = 0.045), and WHtR (B= -0.01, 95% CI (-0.02; -0.01), P- for trend <0.001). They also had lower probability of having abdominal obesity (OR 0.66, 95% CI (0.52; 0.85), P- for trend =0.001). Inverse associations were observed between flavonoids from cocoa powder and BMI z-score (B= -0.08, 95% CI (-0.12; -0.05), P <0.001), WC z-score (B= -0.06, 95% CI (-0.11; -0.02), P =0.003), WHtR (B= -0.01, 95% CI (-0.01; -0.00), P <0.001), %FM (B= -1.11, 95% CI (-1.48; -0.75), P <0.001), and FMI z-score (B= -0.18, 95% CI (-0.20; -0.17), P <0.001). Regarding dark chocolate, an inverse association only with WC z-score (B= -0.06, 95% CI (-0.08; -0.05), P <0.001) was found. However, no association was observed between flavonoids from milk chocolate intake and anthropometric parameters.